2015
DOI: 10.1037/pmu0000109
|View full text |Cite
|
Sign up to set email alerts
|

Perceived suitability of reverberation in large coupled volume concert halls.

Abstract: Reverberation in coupled volume concert halls can be modified by changing the coupling surface connecting the main hall and the control chamber(s). This study aims at investigating how trained listeners evaluate subtle changes in reverberation of coupled spaces for different musical excerpts. Previous research has focused on acoustical parameters and perceptual limits in coupled volumes. The present study relies on a previously validated architectural parameter describing the sound field behavior before relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…To align with the latest research in this field, the experiment included two modes of reverberation: "running" and "stop-chord". As shown in previous studies, the late part of IRs is associated with reverberation length perception for "stop-chord" while the EDT is more associated with the sense of reverberation length for "running reverberation" [20]. Moreover, Lokki [21] obtained two distinctly different assessments of reverberation length depending on the musical excerpt used during the test and suggested that one measure (EDT) cannot predict the difference between "running" and "stop-chord" reverberances.…”
Section: Stimulimentioning
confidence: 69%
“…To align with the latest research in this field, the experiment included two modes of reverberation: "running" and "stop-chord". As shown in previous studies, the late part of IRs is associated with reverberation length perception for "stop-chord" while the EDT is more associated with the sense of reverberation length for "running reverberation" [20]. Moreover, Lokki [21] obtained two distinctly different assessments of reverberation length depending on the musical excerpt used during the test and suggested that one measure (EDT) cannot predict the difference between "running" and "stop-chord" reverberances.…”
Section: Stimulimentioning
confidence: 69%
“…In their study of listener preferences for halls, “Relationships Between Perceived Room Acoustic Quality and Perceived Reverberance, Listener Envelopment, and Tonal Quality,” Acadia Kocher and Michelle Vigeant (2015) investigate how preference judgments for a performance space depend on an interaction between different acoustical attributes of the hall and the particular musical work being heard. Paul Luizard et al (2015; “Perceived Suitability of Reverberation in Large Coupled Volume Concert Halls”) investigate the listener preference for different temporal reverberation characteristics that exist in special concert hall designs where the reverberation can be controlled by operating doors that couple secondary volumes to the concert hall’s main volume. The final paper by Anne Minors and Carlo Harvey (2015; “Influence of Active Listening on the Eye Movement While Viewing Images of Different Concert Halls”) literally looks at a wider picture of concert hall acoustics.…”
Section: Organization Of the Contributions: The Communication Chainmentioning
confidence: 99%
“…Several of these studies involved only a single, simple, and potentially unpleasant and unfamiliar reverberator [22,29] [25] [15,16], sometimes without the use of early reflections [2,17] or stereo capabilities [6,18]. In some cases, the number of reverberator parameters were limited, often taking a restricted range or set of values [19][20][21], and applied to a single (type of) source sample [22][23][24]. In [3,25] the parameter values considered were set by unskilled participants using unfamiliar tools and inferior listening environments.…”
Section: Introductionmentioning
confidence: 99%
“…Very little work is available on novel, more intuitive interfaces for reverb [13,14] and mapping terms to its parameters [4,5]. A number of studies have looked at perception of reverberation in musical contexts [2,6,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], see Table 1.…”
Section: Introductionmentioning
confidence: 99%